Tow rope length and arrangement design for a towed ship - Zan, Umar Imraan (2014)
This research presents the investigation on the effect of different tow rope lengths and arrangements for a towed ship in calm water by using the experimental model conducted at Marine Technology Centre, Universiti Teknologi Malaysia. Three variations of tow rope arrangements were tested in the experiment: Straighttow, V-tow and Kite-tow. A total of fourteen types of tow rope arrangements were tested at a constant speed of 0.5 m/s and a rake-barge were captured via Qualysis Track Manager (QTM) „Image Processing Techniques?. From the experiment, it was observed that for Straight-tow, the tow rope length increment was proportional to the oscillation where for every increment of Lv length (length of tow rope in V shape arrangement) reduced the oscillations by around 12%. Kite-tow arrangement design offered a better safety towing system and has nearly zero sway motion but large water width due to the drift distance from the tow point which is around 0.64 and 1.1 times barge length. The result from Straight-tow with different skegs arrangement s showed significant improvement in reducing the sway motion pf the towed barge. Similarly, V-tow barge with different skegs arrangements also presented a substantial improvement in decreasing the amount of sway motion. In the final part of the research, computer simulation using FORTRAN program and codes from Yasukawa & Fitriadhy (2010) were carried out and the results were compared with the experimental model of Straight-tow barge. Computer simulations and model experiment results showed less than 10% deviation in sway motions.